Pilihan Bahasa Bali pada Komunitas Usia Muda di Kelurahan Monjok Barat Kecamatan Nusa Tenggara Barat - Putu Oktarini; Ni Made Dhananwaty; Ni Made Suryati (Program Magister Linguistik Universitas Udayana, 2021)
The study, entitled “Selection of Balinese language in Young People community Monjok Barat Village, Selaparang District, Nusa Tenggara Barat” is explained how to the speech selection of Balinese language in young people community Monjok Barat village in choosing the language to interact with domain different people in a variety of interest that exits. The research aims at describing the language choosing the speech Bali community. The theories used in this study are speech community theory stated language choice of theory by Fasold . Source of data obtained from the speech at the event said in the family realm, social realm, employment realm, religious realm, art realm. The technique used to process the data that refer to the method and competent method. Data analysis used to process the data that distribusional method or agih method and padan method. The technique and method presentation of analysis result used to formal method and informal method. The research finds the occurrence selection of language in 5 realm are family realm, social realm, religious realm, employment realm and art realm. Selection of language used by young people have difference in each realm. The selection of language used by generation of young people uses Indonesian language more than Balinese language,